BENCANA SEBAGAI SUNNATULLAH: KAJIAN HADIS TENTANG KETETAPAN ILAHI - Siregar, Paisal; Ginting, Ernawati Beru (UIN Sumatera Utara Medan, 2025)
Natural disasters are phenomena that have consistently appeared throughout human history and have often generated diverse theological interpretations within society. Disasters are frequently understood in a fatalistic manner or solely associated with divine wrath, thereby neglecting the dimensions of wisdom and human responsibility. This article aims to examine the concept of disaster as sunnatullah (divine law) from the perspective of the Prophet’s hadiths, particularly within the framework of divine decree (qaḍā’ and qadar). This study employs a qualitative library-based method using a thematic (maudhu‘i) hadith approach, involving the identification, classification, and analysis of hadiths related to calamities, trials, and God’s decree. The findings indicate that the Prophet’s hadiths position disasters as part of sunnatullah, rich in meaning as tests of faith, means of expiating sins, and instruments of spiritual education for humanity. These hadiths also emphasize a balance between divine decree and human effort (ikhtiar), thereby rejecting passive fatalistic understandings. Understanding disasters as sunnatullah in the hadith literature has implications for strengthening patience, promoting active trust in God (tawakkul), and fostering social responsibility in responding to disasters. Accordingly, this study is expected to contribute both theologically and practically to the development of a more contextual, humanistic, and relevant understanding of hadith in relation to contemporary disaster realities.